Pengaruh Metode Pembelajaran Dosen Terhadap Keterampilan Mengajar Mahasiswa - Ana Fitriana; Nikki Tri Sakung; Nina Ikhwati Wahidah (Peneliti.net, 2022)
Competency standards needed by a lecturer in carrying out their work require the lecturer to master the curriculum, learning material, education policies, understanding the characteristics and content of learning materials, mastering the concept, understanding the context of science with society and the environment, the impact and realization of that knowledge in the life of society . This study aims to determine the effect of the methode of lecturer learning on student teaching skills. This research is quantitative. The conclusion of this study is that there is a significant influence between the Quality of lecturer learning with student teaching skills. Based on Anova's table image, it is known that the value of Sig = 0.029 <0.05. If the value of Sig <from α (0.05) then Ho is rejected. That is, the variable teaching skills of students are affected by the quality of lecturer learning